2020
DOI: 10.1038/s41598-020-66695-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of host immune responses to LPS in human using an immune profiling panel, in vivo endotoxemia versus ex vivo stimulation

Abstract: Patients that suffer from sepsis exhibit an early hyper-inflammatory immune response which can lead to organ failure and death. In our study, we assessed the immune modulation in the human in vivo endotoxemia model and compared it to ex vivo LPS stimulation using 38 transcriptomic markers. Blood was collected before and after 4 hours of LPS challenge and tested with the Immune Profiling Panel (IPP) using the FilmArray system. The use of IPP showed that markers from the innate immunity dominated the response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Additionally, experimental studies confirmed that alterations in inflammation and kynurenine metabolism can lead to depressive-like behavior. This has been established in animal models [ 37 ] and human volunteers injected with endotoxin to stimulate inflammation [ 38 ]. It is known that interferon- α injections, to treat hepatitis C, lead to depressive symptoms, together with an increase in cytokines and QUIN in the CSF [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, experimental studies confirmed that alterations in inflammation and kynurenine metabolism can lead to depressive-like behavior. This has been established in animal models [ 37 ] and human volunteers injected with endotoxin to stimulate inflammation [ 38 ]. It is known that interferon- α injections, to treat hepatitis C, lead to depressive symptoms, together with an increase in cytokines and QUIN in the CSF [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, two mitogens were used to evaluate the immunomodulatory effects of the Imuno TF ® : LPS and Con A. Both LPS and Con A are widely used in in vitro and in vivo tests to assess the ability of cells to secrete various types of cytokines [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…LPS, also known as endotoxin, is one of the most potent immunostimulants ( Alexander and Rietschel, 2001 ) and consists of a glycan polymer, oligosaccharide core, and membrane-anchor lipid ( Alexander and Rietschel, 2001 ; Cavaillon, 2018 ). Physiological recognition of the lipid component by the immune system causes pro-inflammatory cytokine activity ( Alexander and Rietschel, 2001 ; Liu et al., 2018 ; Monguió-Tortajada et al., 2018 ; Tawfik et al., 2020 ). Endotoxin is the main driver of pro- and anti-inflammatory cytokine activation in gram-negative bacterial infections ( Feezor et al., 2003 ; Tawfik et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Physiological recognition of the lipid component by the immune system causes pro-inflammatory cytokine activity ( Alexander and Rietschel, 2001 ; Liu et al., 2018 ; Monguió-Tortajada et al., 2018 ; Tawfik et al., 2020 ). Endotoxin is the main driver of pro- and anti-inflammatory cytokine activation in gram-negative bacterial infections ( Feezor et al., 2003 ; Tawfik et al., 2020 ). Endotoxin-induced inflammatory conditions cause similar levels of cytokine expression as those found in septic conditions due to a gram-positive bacteria such as S. aureus , one of the most common bacteria found on the surface of human skin ( Foster, 2004 ; Tawfik et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation